Technology in education : technology-mediated proactive learning : second International Conference, ICTE 2015, Hong Kong, China, July 2-4, 2015, Revised selected papers /: technology-mediated proactive learning : second International Conference, ICTE 2015, Hong Kong, China, July 2-4, 2015, Revised selected papers. (2015) - Unknown
No abstract available